2007
DOI: 10.1200/jco.2006.10.4067
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Patients With Prostate Cancer Who Benefit From Immediate Postoperative Radiotherapy: EORTC 22911

Abstract: Provided careful pathology of the prostatectomy is performed, our results suggest that immediate postoperative radiotherapy might not be recommended for prostate cancer patients with negative surgical margins. These findings require validation on an independent data set.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
146
1
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 274 publications
(155 citation statements)
references
References 41 publications
5
146
1
3
Order By: Relevance
“…6 The effectiveness of adjuvant radiation therapy in preventing PSA relapse and metastasis has been described in several retrospective 7,8,9 and prospective 10,11 studies, with some studies also attempting to determine factors that would predispose patients to a positive response to adjuvant therapy. [12][13][14] The long-term follow-up of the Southwest Oncology Group adjuvant radiation therapy trial (SWOG 8794/RTOG 9019) with 12-year data 15 16 Given the modest duration of this study's follow-up, the long-term risk of metastatic disease is not yet known.…”
Section: Resultsmentioning
confidence: 99%
“…6 The effectiveness of adjuvant radiation therapy in preventing PSA relapse and metastasis has been described in several retrospective 7,8,9 and prospective 10,11 studies, with some studies also attempting to determine factors that would predispose patients to a positive response to adjuvant therapy. [12][13][14] The long-term follow-up of the Southwest Oncology Group adjuvant radiation therapy trial (SWOG 8794/RTOG 9019) with 12-year data 15 16 Given the modest duration of this study's follow-up, the long-term risk of metastatic disease is not yet known.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, a subset analysis of the European Organization for Research and Treatment of Cancer randomized trial 22911 found that the presence of a positive margin was the strongest predictor of prolonged BCR-free survival in patients who received adjuvant RT after RRP, although in the manuscript the authors also conceded that 'it is not certain that PSMs add to the risk of actual local recurrence or systemic disease.' 31 Meanwhile, a recent retrospective investigation noted improved overall survival in patients with organconfined, margin-positive disease who received adjuvant RT, although only 17 patients were included in the treatment group. 32 Further fueling the controversy regarding the timing of secondary treatment for patients with a positive margin at RRP are contemporary data, suggesting that SP 33 and prostate cancer mortality 34 may be decreased with the administration of salvage RT in patients who experience BCR after RRP.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, other studies have shown that patients with a positive surgical margin might benefit more from radiation therapy than patients with a negative margin but who had other risk factors, such as ECE or seminal vesicle invasion. 32 This suggests that predictors for success of Figure 2 Nomogram for the prediction of biochemical recurrence (BCR) after radical prostatectomy. Instructions: draw a perpendicular line from the patient's value to the 'Points' scale on the top of the nomogram.…”
Section: Discussionmentioning
confidence: 99%